2005
DOI: 10.1111/j.1365-2443.2005.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional overlap between RecA and MgsA (RarA) in the rescue of stalled replication forks in Escherichia coli

Abstract: Escherichia coli RecA protein plays a role in DNA homologous recombination, recombination repair, and the rescue of stalled or collapsed replication forks. The mgsA ( rarA ) gene encodes a highly conserved DNAdependent ATPase, whose yeast orthologue, MGS1 , plays a role in maintaining genomic stability. In this study, we show a functional relationship between mgsA and recA during DNA replication. The mgsA recA double mutant grows more slowly and has lower viability than a recA single mutant, but they are equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 60 publications
3
53
0
Order By: Relevance
“…Our results showed that T. kodakaraensis cells are originally more sensitive to UV, as compared to other archaeal species, such as S. solfataricus (Wood et al, 1997), H. volcani (McCready, 1996, and Halobacterium sp. NRC-1 (Baliga et al, 2004), and are also more sensitive than typical model organisms, such as E. coli (Shibata et al, 2005), and Saccharomyces cerevisiae (Hishida et al, 2002). The higher sensitivity of T. kodakaraensis to UV can be rationalized by considering that this organism was isolated from the bottom of the sea, an environment far from UV sources (Morikawa et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that T. kodakaraensis cells are originally more sensitive to UV, as compared to other archaeal species, such as S. solfataricus (Wood et al, 1997), H. volcani (McCready, 1996, and Halobacterium sp. NRC-1 (Baliga et al, 2004), and are also more sensitive than typical model organisms, such as E. coli (Shibata et al, 2005), and Saccharomyces cerevisiae (Hishida et al, 2002). The higher sensitivity of T. kodakaraensis to UV can be rationalized by considering that this organism was isolated from the bottom of the sea, an environment far from UV sources (Morikawa et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of recA Mutant-A library of recA mutants was generated by carrying out PCR-mediated random mutagenesis, as described previously (36). The resultant recA mutant clones were transformed into a recA strain.…”
Section: Methodsmentioning
confidence: 99%
“…Mitomycin C (2.5 mg/ml) was dissolved in 10 mM Tris-HCl (pH 8.5) buffer. Sensitivity to UV damage was measured as described previously (36). To measure sensitivity to MMC, cultures were grown in LB broth to an A 650 of ϳ0.4, serially diluted, spotted onto LB medium containing the indicated concentration of MMC, and incubated at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kan gene flanked by flippase recognition target (FRT) was then eliminated using the flippase helper plasmid pCP20 (Datsenko and Wanner, 2000). The temperaturesensitive dnaE486 mutation of TS1502 (Shibata et al, 2005) was cotransduced with the tetracycline resistance gene of Tn10 into recipient strains at 30°C. Temperaturesensitive colonies were selected among tetracyclineresistant transductants, yielding MK7146 from MK7136 and MK7149 from MK7140.…”
Section: Methodsmentioning
confidence: 99%